Still struggling: intersectionality, vulnerability, and long-term recovery after the Tuscaloosa, Alabama USA Tornado. Issue 4 (1st October 2020) - Prohaska, Ariane
ABSTRACT: This research explores the impact of the Tuscaloosa tornado on the long-term financial and emotional well-being of survivors 4 to 5 years after the event. Using social stress theory and an intersectional analytic approach, this research utilizes in-depth interviews to assess the recovery experiences of survivors. Findings reveal that the tornado resulted in qualitatively different emotional and financial impacts for marginalized Tuscaloosa, Alabama tornado survivors compared to their better situated counterparts, and created unique challenges for Latina survivors. Findings from this analysis can assist emergency managers and service providers in planning for long-term recovery for citizens from multiple diverse backgrounds.